2019
DOI: 10.1186/s12933-019-0824-2
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA-21 is an early predictor of ROS-mediated damage in subjects with high risk of developing diabetes and in drug-naïve T2D

Abstract: Background Impaired glucose tolerance (IGT) is a risk factor for the development of diabetes and related complications that ensue. Early identification of at-risk individuals might be beneficial to reduce or delay the progression of diabetes and its related complications. Recently, microRNAs emerged as potential biomarkers of diseases. The aim of the present study was to evaluate microRNA-21 as a potential biomarker for the risk of developing diabetes in adults with IGT and to investigate its down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 49 publications
2
61
2
4
Order By: Relevance
“…Furthermore, in IGT and T2D subjects there was a significant overproduction of ROS, detected by Electron Paramagnetic Resonance (EPR), an accumulation of lipid peroxidation marker 4-HNE (4-Hydroxynonemal) and defective SOD2 antioxidant response. These results suggest that miR-21 is an early predictor of ROS damage prior to the onset of diabetes and could represent a promising biomarker and a therapeutic target as well [72].…”
Section: Mirnas Oxidative Stress and Diabetic Complicationsmentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, in IGT and T2D subjects there was a significant overproduction of ROS, detected by Electron Paramagnetic Resonance (EPR), an accumulation of lipid peroxidation marker 4-HNE (4-Hydroxynonemal) and defective SOD2 antioxidant response. These results suggest that miR-21 is an early predictor of ROS damage prior to the onset of diabetes and could represent a promising biomarker and a therapeutic target as well [72].…”
Section: Mirnas Oxidative Stress and Diabetic Complicationsmentioning
confidence: 84%
“…MiR-21 has also been demonstrated to be hyperexpressed in HUVEC (Human Umbelical Vein Endothelial Cells) cells uponconstant or oscillating high glucose exposure, and its upregulation is able to inhibit expression and function of several specific target genes such as KRIT1(Krev/Rap1 Interaction Trapped-1), NRF2 (Nuclear Factor erythroid Related Factor 2), and SOD2 (Superoxide Dismutase 2) (which have anti-oxidant functions), thus generating mitochondrial dysfunction. Circulating miR-21 was also found upregulated in T1D, T2D, and in IGT patients, in which increased ROS production has been observed [72]. Moreover, as antagomiR-21 conveyed with different NPs resulted in efficient uptake by target tissue, a miR-21 nano-based drug could also be promising for diabetes therapies targeting oxidative stress.…”
Section: Clinical Advancements Of Mirna-based Drugsmentioning
confidence: 92%
“…miRNAs have been proposed as surrogate markers of the prediabetes state, 38,39 diabetes and cardiovascular complications, 40 being detectable in a stable form in blood circulation and biological fluids. Many studies have revised the involvement of miRNAs in the vascular complications of diabetes 29 as well as in atherosclerosis, 41 determining a branch of investigation deserving special attention due to potential diagnostic and therapeutic implications.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Interestingly, other studies by La Sala et al confirmed that elevated levels of miR-21 are associated with increased abundance of ROS and reduced SOD2 antioxidant defense. Moreover, the authors suggested that miR-21 might serve as a predictive parameter for the early detection of glucose imbalances in prediabetic patients [224]. There is also a strong link between obesity and miR-21.…”
Section: Mirnas In Mets-a Link With Obesity and Insulin Resistance/hymentioning
confidence: 99%